(3TQM fRgI GdfXGQ aj UfGYI GdZHGQs - (3CMeO Hf eMeO Hf LHQjd GdeZQHjs; (3GHf GdgGFe , TgGH GdOjf CHh GdYHGS GdefUhQj,J (B887 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdHGQi GdfSe GdYGOd ajeG bSe s
(3BNQgG (B:s
(3hef QGe Gi WdH GdJHMQ Gi GdJhSY aYdjg HGdeYhfI Ci GdcJGH GdeSei HGdeYhfg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B220s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B59 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3QjGVjGJ (B1016) s
Keywords: (3GdQjGVjGJs